Spatial and temporal variations of radon concentrations in groundwater of hard rock aquifers in Madurai district, India - Thivya, C.; Chidambaram, S.; Thilagavathi, R.; Tirumalesh, K.; Nepolian, M.; Prasanna, Mohan Viswanathan (Akademiai Kiado Rt., 2017)
Radon (222Rn) and other radionuclides in groundwater can lead to health problems if present in higher concentrations. A study was carried out in Madurai district of Tamilnadu by collecting groundwater samples for four different seasons and aims to identify the regions with higher 222Rn concentration along with their spatial and seasonal variations. 222Rn has been compared with field parameters, log pCO2, major ions and uranium to detect the factors responsible for the higher concentration in groundwater. The weathering process induces the release of higher uranium ions from the granitic terrain from the rock matrix which enhances the 222Rn levels in groundwater.